TEACHING ENGLISH FOR SPECIFIC PURPOSES (ESP) AT ENSTP- 1ST YEAR ENGINEERING STUDENTS- - Naima Amalou, Soraya Hamane, (Chelonian Research Foundation, 2022)
English for Specific Purposes (ESP) is a distinct division or subset of English education for non-native speakers. It primarily focuses on instructing university students or employed individuals, catering to their specific needs by emphasizing relevant vocabulary and skills. Algeria implemented English instruction using ESP at all educational levels, especially in universities. ESP, which is specifically designed to fulfil the needs of a given specialization of the students has become one of the widely used techniques to teach English for 1st year students at National School of Built and Ground Works Engineering (ENSTP), basing mainly on the needs analysis and materials evaluation. To ensure that, this Technical English course should meet needs assessment with engineering themes to better understand specific topics, and methodology to be included in the course to acquiring a more profound comprehension of various disciplines of ground works through communicative learning techniques in the class. ESP teachers’ design courses usually adopt the approaches that can be distinguished by language-focused, skill-focused, and learning-focused approaches. Key Words: ESP; ENSTP; learning centred; needs analysis; skills-centred.